Accidentally ever after eaudiobook - Cassidy, Dakota (Accidentally Paranormal, 2016)
Antonia Vitali's on the run and in hiding, working as a salesclerk in a designer outlet mall in Jersey. Toni's life has been on a steady downward decline for three years now, the ghosts of her past always nipping at her heels. Little does she know, her life's about to change when the OOPS girls whisk in for a day of Christmas shopping and fall through a wormhole in the store's dressing room, taking Toni with them . . . Now Toni's got a pair of sparkly purple heels gifted to her by the Good Witch of the South—gorgeous heels she can't take off until she returns them to the king. With a trio of reluctant fairy godmothers and an ogre named Dannan, Toni's on a mission to get to the castle to receive a happily-ever-after she never asked for. Along the way, she meets an amazingly handsome, utterly chiseled stable boy named Jon Doe, who offers to help them navigate the Not So Sherwood Forest and get them all to Castle Beckett before Christmas Eve. Join Toni, Marty, Nina, Wanda, and Carl, as they journey along the treacherous road to love and eternal happiness in the magical realm of Shamalot.